2003
DOI: 10.1016/s1074-5521(03)00092-9
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Gene Cluster from Streptomyces nanchangensis NS3226 Encoding Biosynthesis of the Polyether Ionophore Nanchangmycin

Abstract: The PKS genes for biosynthesis of the polyether nanchangmycin are organized to encode two sets of proteins (six and seven ORFs, respectively), but are separated by independent ORFs that encode an epimerase, epoxidase, and epoxide hydrolase, and, notably, an independent ACP. One of the PKS modules lacks a corresponding ACP. We propose that the process of oxidative cyclization to form the polyether structure occurs when the polyketide chain is still anchored on the independent ACP before release. 4-O-methyl-L-rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 53 publications
1
111
0
3
Order By: Relevance
“…This nonladder polyether provided the first example of a sequenced Type I PKS polyether gene cluster (Leadlay et al, 2001). The only other nonladder polyether with a sequenced Type I PKS gene cluster is nanchangmycin (Sun et al, 2003). The biosynthetic process for both of these polyethers includes ketoreductases and dehydratases for the formation of the backbone carbon-carbon double bonds.…”
Section: Polyketide Biosynthesis At the Molecular Levelmentioning
confidence: 98%
“…This nonladder polyether provided the first example of a sequenced Type I PKS polyether gene cluster (Leadlay et al, 2001). The only other nonladder polyether with a sequenced Type I PKS gene cluster is nanchangmycin (Sun et al, 2003). The biosynthetic process for both of these polyethers includes ketoreductases and dehydratases for the formation of the backbone carbon-carbon double bonds.…”
Section: Polyketide Biosynthesis At the Molecular Levelmentioning
confidence: 98%
“…To date, three gene clusters for the ionophore antibiotics, monensin, 13) nanchangmycin 16) and nigericin, 17) have been identified. Based on a series of gene disruption experiments, 14,15) it has been established that epoxidase and epoxide hydrolase were the key enzymes in monensin biosynthesis.…”
Section: Sequential Cyclic Ether Formationmentioning
confidence: 99%
“…The similar fused type of epoxide hydrolase gene, nanI, has been found in the biosynthetic gene cluster of nanchangmycin. 16) As mentioned in the introduction, all the gene clusters reported are APPA-type polyethers (monensintype), 13,16,17) and there is no report on a gene cluster of a PAPA-type polyether, although the 4.5 kb partial sequence of a putative PKS gene responsible for the biosynthesis of salinomycin has been reported. 52); * In this study, we found the first gene cluster for the PAPA-type polyether, lasalocid.…”
Section: Sequential Cyclic Ether Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme encoded pldD was perhaps 18, 19-epoxydase, because pldD shows strong similarity to monCI (monensin epoxidase) 21) and NanO (nanchangmycin epoxidase). 22) The amino acid sequence of pldC showed significant homology to that of Rif-Orf20 which is involved in the rifamycin biosynthetic gene cluster of Amycolatopsis mediterranei S699. 23) Since the Rif-Orf20 product is rifamycin 25-O-acetylase, 24) the pldC gene probably encodes an enzyme belonging to the CoA-dependent acyltransferase family and to catalyze pladienolide 7-Oacetylation.…”
Section: Features Of the Pladienolide Biosynthesis Clustermentioning
confidence: 99%